2018
DOI: 10.17011/ht/urn.201811224837
|View full text |Cite
|
Sign up to set email alerts
|

"I use it correctly!": The use of ICTs among Italian grandmothers in a generational perspective

Abstract: In this project, we investigated the role played by digital media and information and communication technologies (ICTs) in building intergenerational and intragenerational relations for grandparents. Specifically, we investigated the possible relationships between grandmothers, children, and grandchildren, with the aim of understanding the dynamics of intergenerational exchanges and how grandmothers experience the use of the Internet as a tool to facilitate communication with family members. The research shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
(27 reference statements)
1
18
0
1
Order By: Relevance
“…Thus, guidelines for health care workers do not fall under the jurisdiction of the health agency. When targeting elderly people, considerations regarding the digital divide (i.e., technology use is less common in older vs. younger populations) may have affected agencies’ online communication in Italy and the United States ( Colombo et al, 2018 ), the elderly social group was targeted at low rates in these communications. Conversely, in Sweden, 96% of people between the ages 65 and 74 years, and 77% of people between the ages 75 and 84 years, use the internet ( Statistiska centralbyrån, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, guidelines for health care workers do not fall under the jurisdiction of the health agency. When targeting elderly people, considerations regarding the digital divide (i.e., technology use is less common in older vs. younger populations) may have affected agencies’ online communication in Italy and the United States ( Colombo et al, 2018 ), the elderly social group was targeted at low rates in these communications. Conversely, in Sweden, 96% of people between the ages 65 and 74 years, and 77% of people between the ages 75 and 84 years, use the internet ( Statistiska centralbyrån, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because the socialization tools of their eras and their practices related to life resulted in not growing with up this technology, lack of skills to use this technology and low level of motivation to acquire and use this technology. Yet, many studies demonstrate that many individuals aged 60 and over hold on to the life and cope with loneliness by using this new technology, have high level of motivation to use this new technology and are aware of recent developments (Colombo et al, 2018;Olphert & Damodaran, 2013;Paul & Stegbauer, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although this study was inspired and developed from the study of Colombo, Aroldi & Carlo (2018) on "Italian Grandmothers", the male elders were also included in this study. A qualitative study was conducted by means of techno-biography in order to find out the subjective experiences in digital technology use of participants in the research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, burgeoning research, especially in the fields of HCI, aging, and technology (Abascal & Civit, 2001;Plaza, Martin, Martin, & Medrano, 2011), has been conducted on smartphones and older adults due to the rising aging population worldwide. Other studies revealed that older adults are active smartphone users (Colombo, Aroldi, & Carlo, 2018;Rosales & Fernández-Ardèvol, 2016a;Selwyn, Gorard, Furlong, & Madden, 2003). A majority of older adults, especially those in the young-old cohort, aged 60 to 74 (Fisk et al, 2009), are considered still productive and active at their age, having special information and communication technology (ICT)-related needs, and are interested in learning new technology, including smartphone and mobile apps (Berenguer et al, 2017;Carlsson & Walden, 2015;Nikou, 2015;Rosales & Fernández-Ardèvol, 2016a).…”
Section: Smartphone Mobile Apps and Older Adultsmentioning
confidence: 99%